2021
DOI: 10.3390/en14185788
|View full text |Cite
|
Sign up to set email alerts
|

Spraying and Mixing Characteristics of Urea in a Static Mixer Applied Marine SCR System

Abstract: The most effective de-NOx technology in marine diesel applications is the urea-based selective catalytic reduction (SCR) system. The urea-SCR system works by injecting a urea solution into exhaust gas and converting this to NH3 and CO2. The injection, mixing, and NH3 conversion reaction behavior of the urea-water solution all have a decisive effect on the performance of the system. To improve de-NOx efficiency, it is important to provide enough time and distance for NH3 conversion and uniform distribution prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Hui et al [18] pointed out that it is difficult to achieve the uniform distribution of NH 3 using hole-type UWS injectors. While, Jang et al [19] observed a decrease in exhaust gas temperature in a marine SCR system equipped with a mixer, along with a rise in the ammonia concentration. This was attributed to the endothermic thermolysis reaction and the increased area where the reaction took place.…”
Section: Introductionmentioning
confidence: 97%
“…Hui et al [18] pointed out that it is difficult to achieve the uniform distribution of NH 3 using hole-type UWS injectors. While, Jang et al [19] observed a decrease in exhaust gas temperature in a marine SCR system equipped with a mixer, along with a rise in the ammonia concentration. This was attributed to the endothermic thermolysis reaction and the increased area where the reaction took place.…”
Section: Introductionmentioning
confidence: 97%
“…7 The amount of urea required by the marine SCR system is larger, which is more likely to cause excessive ammonia escape. 8 Model predictive control (MPC) is a sampling control algorithm based on object model. It can deal with complex control problems with constrained control action and solve the hysteresis problem.…”
Section: Introductionmentioning
confidence: 99%
“…7 The amount of urea required by the marine SCR system is larger, which is more likely to cause excessive ammonia escape. 8…”
Section: Introductionmentioning
confidence: 99%